2019
DOI: 10.1186/s12960-019-0393-1
|View full text |Cite
|
Sign up to set email alerts
|

Medical diaspora: an underused entity in low- and middle-income countries’ health system development

Abstract: Background At present, over 215 million people live outside their countries of birth, many of which are referred to as diaspora—those that live in host countries but maintain strong sentimental and material links with their countries of origin, their homelands. The critical shortage of Human Resources for Health (HRH) in many developing countries remains a barrier to attaining their health system goals. Usage of medical diaspora can be one way to meet this need. A growing number of policy-makers h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Our leveraging of the Yemeni diaspora echoes recent recognition of the potential value of this strategy for health system development (Frehywot et al, 2019).…”
Section: Culturementioning
confidence: 69%
“…Our leveraging of the Yemeni diaspora echoes recent recognition of the potential value of this strategy for health system development (Frehywot et al, 2019).…”
Section: Culturementioning
confidence: 69%
“…Anand et al in 2009 describe how diaspora scientists in the USA feel personally accountable to both the U.S. and their origin country institutions, which can help with research and training collaborations among the two for capacity building [ 48 ]. Frehywot et al in 2019 published an inventory of low- and middle-income countries’ medical diaspora organizations from the USA, the UK, Canada, and Australia, showing a trend in three focuses of these organizations: providing healthcare services, training, and humanitarian aid when needed to their origin country; creating professional networks of migrant physicians; and supplying improved and culturally sensitive healthcare to the migrant population within the host country [ 13 ]. The lack of available data on diaspora organizations, however, remains a limitation in the identification and analysis of these efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Some of their activities focused on short-term humanitarian needs, but others had longer time frames and health system priorities. That study also found 68 LMICs that had set up diaspora offices to help coordinate or manage diaspora contributions [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…These promising efforts can provide the foundation for community response and should be scaled up and expanded to all regions in the country. Sudanese physicians in the diaspora played a significant role in guiding these efforts as well as providing training, capacity building, technical support, and transfer of knowledge [ 19 , 32 ]. …”
Section: Suggested Strategies For Preventing Future Peaksmentioning
confidence: 99%
“…Sudanese physicians in the diaspora played a significant role in guiding these efforts as well as providing training, capacity building, technical support, and transfer of knowledge [ 19 , 32 ].…”
Section: Suggested Strategies For Preventing Future Peaksmentioning
confidence: 99%